Strategi Pemasaran Dan Promosi Secara Online Melalui Instagram Di Cimory On The Valley - Pertiwi, Fides Garda; Nivak, Christian Lilik HS (JURNAL DESTINASI PARIWISATA, 2021)
Nowadays, with social media, promoting and marketing product is fairly easy, especially for tourism products and activities. The social media currently popular among the public is Instagram. With Instagram we can provide information about tourism in the form of photos and videos. Instagram has many features that can facilitate promotion and marketing so that the products we market can be reached even to the world community. However, all of that requires a strategy that is maximal enough so that the information we provide is precise and maximal. Based on this, researchers are interested in researching how the marketing strategy at tourist attractions in Cimory On The Valley through their Instagram social media. In this study, researchers used descriptive qualitative methods and conducted interviews with Instagram managers and tourists from Cimory On The Valley for data collection. This study aims to determine marketing and promotion strategies in Cimory On The Valley through social media Instagram, and also to provide empirical evidence that marketing and promotion strategies through Instagram social media have an effect on Cimory On The Valley. After knowing the strategies and results of the strategies that have been carried out by Cimory On The Valley in marketing through its Instagram, the researchers also provided several strategic recommendations that could be done to maximize marketing, such as content consistency, interaction with followers, content with prizes, and many more. Keyword: Digital Marketing, Tourism Destination, Instagram